THE SOUND OF IMAGE MORPHOGENESIS - Adrian BORZA (Studia Universitatis Babeş-Bolyai. Musica, 2015)
The challenging side of the spectral synthesis is to integrate an advanced and versatile technology into music composition, which brings a twist in computer synthesis, that is, the sound of image morphogenesis. The genesis of the sound object resides in visual forms, by assigning sound qualities – pitch, duration, loudness and panning – to a point or line or surface and to their own brightness and color. As a result, the graphical image is transformed into sounds. In this respect, the author’s works Drones II (2012) and Increat (2003) – the latter inspired by a painting by the visual artist Claudiu Presecan, are examples of music composition positioned on the border of the audio-visual and technology domains.